The cancer survival index—A prognostic score integrating psychosocial and biological factors in patients diagnosed with cancer or haematologic malignancies. (22nd March 2022) - Gaiger, Alexander; Lubowitzki, Simone; Krammer, Katharina; Zeilinger, Elisabeth L.; Acel, Andras; Cenic, Olivera; Schrott, Andrea; Unseld, Matthias; Rassoulian, Anahita Paula; Skrabs, Cathrin; Valent, Peter; Gisslinger, Heinz; et al.
Abstract: Objective: We aimed to investigate whether (1) psychological and social indicators influence survival in patients diagnosed with cancer or haematologic malignancies when important biological aspects are controlled for, (2) psychological, social and biological indicators can be utilised to design one collated index for survival, usable in clinical practice to identify patients at risk of shorter survival and to improve personalised healthcare provision. Methods: In this cross‐sectional study, 2263 patients with cancer or haematologic malignancies participated. We analysed 15 biological, psychological and social indicators as risk factors for survival with a Cox proportional hazards model. Indicators significantly associated with survival were combined to compute models for the identification of patient groups with different risks of death. The training sample contained 1122 patients. Validation samples included the remaining 1141 patients, the total sample, as well as groups with different cancer entities. Results: Five indicators were found to significantly impact survival: Cancer site (HR: 3.56), metastatic disease (HR: 1.88), symptoms of depression (HR: 1.34), female sex (HR: 0.73) and anaemia (HR: 0.48). Combining these indicators to a model, we developed the Cancer Survival Index, identifying three distinct groups of patients with estimated survival times of 47.2 months, 141 months and 198.2 months ( p < 0.001). Post hoc analysis of the influence of depression on survival showed a mediating effect of the following four factors, related to both depression and survival: previous psychiatric conditions, employment status, metastatic disease and haemoglobin levels. Conclusions: Psychosocial and biological factors impact survival in various malignancies and can be utilised jointly to compute an index for estimating the survival of each patient individually—the Cancer Survival Index. Abstract : We analysed 15 biological, psychological and social indicators as risk factors for survival in 2263 cancer patients with a Cox proportional hazards model. Five indicators, that is cancer site, metastatic disease, depression, female sex and anaemia, were significantly associated with survival and combined to compute the Cancer Survival Index.